2020
DOI: 10.2196/17875
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Participation in Clinical Guidelines Development: The Cystic Fibrosis Foundation Experience

Abstract: Patient and family participation in guideline development is neither standardized nor uniformly accepted in the guideline development community, despite the 2011 Institute of Medicine’s Guidelines We Can Trust and the Guideline International Network’s GIN-Public Toolkit recommendations. The Cystic Fibrosis Foundation has included patients and/or family members directly in guideline development since 2004. Over time, various strategies for increasing patient and family member participation have been implemented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…This experience has emphasized the importance of taking into consideration what participants and their families value most when being involved in research studies. Participant and family participation and input in the development of guidelines and methodology can provide insight to clinicians that could be otherwise overlooked [35]. This insight is valuable during the design phase but is still important to consider at all stages of the study, as demonstrated in the methodology outlined in this manuscript.…”
Section: Resource Limitationmentioning
confidence: 96%
“…This experience has emphasized the importance of taking into consideration what participants and their families value most when being involved in research studies. Participant and family participation and input in the development of guidelines and methodology can provide insight to clinicians that could be otherwise overlooked [35]. This insight is valuable during the design phase but is still important to consider at all stages of the study, as demonstrated in the methodology outlined in this manuscript.…”
Section: Resource Limitationmentioning
confidence: 96%
“…Their participation can be through open public forums, surveys on guideline topics, review, and feedback, or as part of guideline committees or focus groups. PwCF and their families add lived experience to guideline creation and their participation has been overwhelmingly positive in improving the guideline creation project [80]. PwCF and their families have partnered with their care team on quality improvement initiatives, providing unique perspectives to improved CF care by working together with a shared aim [81].…”
Section: Coproductionmentioning
confidence: 99%
“…Patient participation in research is increasingly desired in developing relevant health care services. [17][18][19] Some studies used the participation of CF patients in the identification of research priorities, 20 in clinical guideline development, 21 or in a quality improvement program 22 have demonstrated the relevance of the participation of these patients who have a experiential knowledge of their disease. 23 The interests of involving patients, healthcare professionals, and researchers in the co-design of a program aiming at improving medication adherence are multiple.…”
Section: Introductionmentioning
confidence: 99%